Vtify Application / Nurish Shahirah Rosli … [et al.] - Rosli, Nurish Shahirah; Suhaimi, Nur Syuhada; Abdul Halim, Intan Aqilah; Jumat, Alyaa Ameera; Shaari, Nor Shamira; Hanapiyah, Zulkefli Muhamad (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In recent decades, new technologies have had a dramatic impact on the way we live. Not only have new innovations transformed the way we communicate with one another, but they’ve also had a transformative effect on how we go about our daily routines. To provide a better daily life for the special need, this study develops an idea of Vtify which combine the words “vision” and “identify”, demonstrating that application’s capability for identifying objects. Vtify is an innovation for individuals with visual disabilities. To be more precise, Vtify is a mobile application designed to help blind and visually impaired people identify objects in their daily lives and to support them in being more independent in their daily lives. Vtify also utilizes the camera and voiceover capabilities of the smartphone to record pictures or videos. This application provides blind and visually impaired users with an audio to describe the information. Vtify is a multilingual application that supports other languages, making it possible for a wider range of users worldwide to utilize it. Additionally, the application can offer comprehensive details on things, such as usage guidelines and safety precautions, to assist users in comprehending and securely interacting with them. To improve users’ understanding of the objects they come upon, this feature may also include instructional materials.